Inhibition of rat platelet aggregation by mycalolide-B, a novel inhibitor of actin polymerization with a different mechanism of action from cytochalasin-D - Sugidachi, A; Ogawa, T; Asai, F; Saito, S; Ozaki, H; Fusetani, N; Karaki, H; Koike, H (Thrombosis and haemostasis, 1998)
In vitro effects of mycalolide-B (MB), isolated from marine sponge, were investigated with regard to the activation of rat platelets. Collagen-induced platelet aggregation in platelet-rich plasma (PRP) was slightly but significantly potentiated by lower concentrations of MB (0.3 and 1 microM) but was inhibited by higher concentrations (3 and 10 microM). ADP-induced platelet aggregation in PRP was also significantly prevented by MB (1-10 microM). Potentiation of ADP-induced aggregation by MB (0.3 microM) was hardly observed. G-actin contents, determined by DNase I inhibition assay, were increased in resting washed platelets incubated with MB (3 microM). In contrast, cytochalasin-D (CD) at 3 microM slightly reduced G-actin contents in resting platelets. After platelet aggregation with collagen (3 microg/ml) or ADP (10 microM), G-actin contents in platelets were reduced, indicating de novo actin polymerization. MB (3 microM) and CD (3 microM) abolished both ADP (10 microM)- and collagen (3 microg/ml)-induced platelet aggregation and actin polymerization in washed platelets. MB (1-10 microM) had no effects on intracellular Ca2+ concentrations in ADP (10 microM)-stimulated platelets. [125I]-fibrinogen binding to activated platelets with ADP (10 microM)(was inhibited by MB (0.3-3 microM) in a concentration-dependent manner. Thrombin-induced platelet-fibrin clot retraction was inhibited by MB (1 and 10 microM). These results suggest that MB inhibits platelet activation by interfering with actin polymerization through a different mechanism of action from CD. MB may be a useful tool for studying the role of actin polymerization in various cells.